Парикмахер: учебное пособие / [автор - сост. И. В. Мельников] - Мельников И.В. (Профессиональное образование, 2009)
Экземпляры: (16112009) / Инвентарный номер: 45824 / Цена: 105.00 / Сис.шифр: 38.937я7 / Авт.знак: П 18 / ГРНТИ: 75.33.57 / ББК: 38.937я7